A novel true triaxial apparatus for high-stress low-frequency disturbance in hard rocks: Development, validation, and application - Chao Peng; Hanwen Jia; Yang Liu; Huanxin Liu; Xiwei Zhang (PLoS ONE, 2025)
A novel true triaxial apparatus (TTA) has been designed and fabricated to investigate the mechanical behavior of deep underground engineering under high-stress conditions and low-frequency disturbance loads. This apparatus features a two-rigid, one-flexible loading system, with rigid loading applied along the directions of the maximum and intermediate principal stresses, offering maximum load capacities of 2000 kN and 4000 kN, respectively. The direction of the maximum principal stress is also equipped with dynamic loading capabilities, enabling low-frequency disturbance loads with frequencies up to 20 Hz and amplitudes of 0.5 mm. The minimum principal stress direction utilizes flexible loading, with pressure capabilities of up to 120 MPa. Moreover, the integration of a high-rigidity loading frame and high-precision servo control systems has significantly enhanced the apparatus’s performance and data accuracy, particularly in small-scale deformation tests. Additionally, a dual-actuator, dual-loop servo control mode is employed to effectively suppress eccentric loading effects in true triaxial tests. To validate the reliability of the TTA and to preliminarily explore the effects of stress paths and disturbances on deep rock mechanical properties, true triaxial tests were conducted using granite. The results demonstrate that both the intermediate principal stress and disturbance frequency significantly influence the strength and failure modes of the rock. Static and disturbance tests exhibited excellent high repeatability and consistency, further confirming the accuracy and reliability of the apparatus. Overall, the TTA provides a novel methodology for investigating the mechanical properties of deep rock masses under high-stress and low-frequency disturbance conditions, making it an effective tool for addressing related scientific and engineering challenges.